Experimental dynamic identification of modeshape driving wind turbine grid loss event on nacelle testrig. (January 2016) - Helsen, J.; Devriendt, C.; Weijtjens, W.; Guillaume, P.
Abstract: This paper experimentally investigates a grid loss event on the Gearbox Reliability Collaborative drivetrain mounted on the NREL nacelle testrig. It is shown that during the grid loss event the system vibration is driven by a counter phase rotation of the rotor and generator rotor about the drivetrain flexibility. This behavior results in significant torque oscillations with significant negative torque periods. This work shows that at each zero-crossing the teeth disengage contact, go through the backlash and re-engage at the other flank by means of strain gauge measurements at the HSS pinion teeth. The driving torsional resonance is identified by means of a pLSCF modal identification estimator. Challenges for accurate modal parameter estimation related to harmonic excitation are elaborated and tackled. Finally the dominating eigenfrequency, corresponding modeshape and damping value are determined. Highlights: We perform an experimental investigation of a grid loss event on a nacelle test-rig. The first torsional drivetrain mode is determined based on torque measurements. A pLSCF algorithm is used to estimate eigenfrequency, damping and modeshape.